ALUR DAN TEMA DALAM KARYA CHOPIN "THE AWAKENING" - NFN Mustafa (SAWERIGADING, 2012)
This paper aims to describe two aspects of literary works, they are plot and themes in the works of Chopin "The Awakening"'. This paper uses methods of discourse analysis and descriptive interpretation of the structural approach, sociological approach, and intuitive approach. Techniques of collection data is done by using 'Inventory Technique, namely by finding and collecting data is then analyzed further. Data writing is the result of the study characterizations in Chopin "The Awakening"'. The story, tells domestic life with a different culture, American culture (Edna) and French descent "Creole" (Pontallier) which colured by dishonesty story, and hypocrisy. This paper is expected to contribute ideas who are interested primarily in the field of American Literature. Abstrak Tulisan ini bertujuan memaparkan dua aspek karya sastra, yaitu alur dan tema dalam karya Chopin "The Awakening". Tulisan ini menggunakan metode analisis wacana deskriptif interpretasi dan pendekatan struktural, pendekatan sosiologis, dan pendekatan intuitif. Teknik pengumpulan data dilakukan dengan menggunakan 'Inventory technique, yaitu dengan mencari dan mengumpulkan data kemudian dianalisis lebih lanjut. Data penulisan ini adalah hasil kajian penokohan dalam novel "The Awakening" karya Chopin. Ceritanya, berkisah tentang kehidupan rumah tangga dengan budaya yang berbeda, budaya Amerika (Edna) dan Perancis keturunan "Creole" (Pontallier) yang dibumbuhi dengan kisah cinta, perselingkuhan, dan kemunafikan. Tulisan ini, diharapakan dapat memberikan sumbangan pemikiran terutama yang tertarik dalam bidang kesastraan Amerika.